New Cobalt‐Bisterpyridyl Catalysts for Hydrogen Evolution Reaction. Issue 12 (12th June 2017) - Aroua, Safwan; Todorova, Tanya K.; Mougel, Victor; Hommes, Paul; Reissig, Hans‐Ulrich; Fontecave, Marc
Abstract: Preparation of a series of terpyridyl ligands bearing different substituents recently led to the synthesis of new cobalt‐bisterpyridyl complexes spanning over a wide range of redox potentials. In this work, we describe the catalytic properties of these complexes for the electroreduction of protons into hydrogen (hydrogen evolution reaction (HER)) in acetonitrile. The substituents of the ligands were found to greatly affect the catalytic performances of the systems, in terms of stability and overpotential. Interestingly, systems based on dimethylamino‐terpyridine derivatives perform HER with high efficiency, low overpotential and excellent stability. Density functional theory calculations were used to provide insights into the reaction mechanism of HER catalyzed by these systems, highlighting the role of the ligand for proton activation. Abstract : Electrochemical proton reduction : New cobalt bisterpyridyl complexes were studied for the hydrogen evolution reaction, showing the importance of the ligands substituting groups on activity.